Aprendizaje cooperativo como estrategia para mejorar los niveles de comprensión lectora en estudiantes de quinto grado de básica primaria (2019)
The present work establishes the effect of Cooperative Learning for better in the levels of Reading Comprehension in students of fifth grade of primary basic of the Educational Institution Community Center of Basic and Middle Education # 187- Civic April 7. The methodology was framed in a quantitative approach of a quasi-experimental type, applied to a population of 68 students; in which a control group and an experimental group were established, which in the intervention phase, the Cooperative Learning strategy in reading activities was implemented. The results allowed us to rule out the null hypothesis. Therefore, the conclusions highlight that the average in the test that measures the development of the levels of reading comprehension in the students of the experimental group where the classes with the Cooperative Learning were developed is higher than the average in the test that measures the development of reading competence in the area of language for students of the control group where the readings are developed in a traditional way.